Biochemical differences between nano- and normal formulation of tamoxifen and other natural bioactive materials ameliorate breast cancer in experimental rats - Ezzat, Afaf (2023)
Human breast cancer is the most prevalent malignancy in women all-over the world. The aim is to look further into the effectiveness of the nanoformulation of tamoxifen and even certain bioactive compounds (yeast, isoflavone, and silymarin) and their impacts on diminishing the breast cancer progression. A single medication dosage of 7,12-dimethylbenz[a]anthracene (DMBA) was administered intragastrically by fifty-four female Sprague–Dawley rats. After fourteen days of DMBA admission, the procedure protocol actually started out. At long last, all of the experimental findings assessed, tabulated, and statistically analyzed.